P5.096 Estimating the Potential Economic Impact of Antimicrobial Resistance in Neisseria Gonorrhoeae in the United States. (13th July 2013) - Chesson, H; Owusu-Edusei, K; Kirkcaldy, R D; Gift, T L; Weinstock, H S
Abstract : Background: Antimicrobial resistance to treatment can hinder gonorrhoea prevention and control efforts, thereby leading to increases in gonorrhoea incidence. We estimated the economic burden of potential increases in gonorrhoea incidence in the US as a result of emerging cephalosporin resistance. Methods: The potential increase in gonorrhoea due to resistance was based on an analysis of historical gonorrhoea incidence and ciprofloxacin resistance data. We used clinic-level resistance data from the Gonococcal Isolates Surveillance Project (GISP) and city-level gonorrhoea incidence rates from surveillance data for 17 GISP cities from 1991 to 2006. We performed a regression analysis in which the gonorrhoea rate (log) was the dependent variable and the independent variable of interest was the percentage of GISP isolates (from the clinic in the respective city) resistant to ciprofloxacin. To estimate the cost of potential increases in gonorrhoea, we used STIC-Figure, a spreadsheet programme that applies published equations of the economic impact of STDs. Results: The regression analysis found a significant, positive association (p < 0.01) between ciprofloxacin resistance and gonorrhoea incidence at the city level. The results suggested that an increase in resistance from 0% to 10% of isolates could result in a net increase in gonorrhoea of about 7% (range: 3% - 12%) in the first year and 17% (range: 6% - 28%) after ten years. Over ten years, the estimated impact would be substantial: 48, 000 additional cases of PID, 5, 000 additional cases of epididymitis, and 560 additional HIV infections, with direct medical costs totaling 405 million (range: 152 million - 689 million). Conclusions: Ciprofloxacin resistance was associated with increased gonorrhoea rates, despite availability of alternative treatments at the time. Correspondingly, emerging cephalosporin resistance could have substantial health and economic consequences. Efforts to control the spread and reduce the consequences of resistant strains can mitigate this potential burden.